Reallocating water from canal irrigation for environmental flows: benefits forgone in the Upper Ganga Basin in India - Amarasinghe, Upali A.; Smakhtin, Vladimir U.; Bharati, Luna; Malik, Ravinder Paul Singh (Springer, 2013)
This paper assesses the potential loss of irrigation benefits in reallocating water from irrigation to meet requirements for environmental flows (e-flows) in the Upper Ganga Basin (UGB) in northern India. The minimum requirement for e-flows in the UGB is 32 billion cubic meters (BCM), or 42 % of the mean annual runoff. The current runoff during the low-flow months falls below the minimum requirement for e-flows by 5.1 BCM. Depending on irrigation efficiency, reallocation of 41?51 % of the water from canal irrigation withdrawals can meet this deficit in minimum e-flows. The marginal productivity of canal irrigation consumptive water use (CWU), estimated from a panel regression with data from 32 districts from 1991 to 2004, assesses the potential loss of benefits in diverting water away from crop production. In the UGB, canal irrigation contributes to only 8 % of the total CWU of 56 BCM, and the marginal productivity of canal irrigation CWU across districts is also very low, with a median of 0.03 USD/m3. Therefore, at present, the loss of benefits is only 1.2?1.6 % of the gross value of crop production. This loss of benefits can be overcome with an increase in irrigation efficiency or marginal productivity.